KOMPLEKSITAS PERMASALAHAN MERKURI DALAM PENGOLAHAN BIJIH EMAS BERDASARKAN PERSPEKTIF TEKNIS LINGKUNGAN MANUSIA DAN MASA DEPAN - Erry Sumarjono (KURVATEK, 2020)
Mercury is one of the most dangerous heavy metal. It has highest negative effects to human and environment. It has advantage to extract gold from it’s ore, because, naturally, the character of Mercury had high affinity with Gold particle. It is very easy to use Mercury to extract Gold from it’s ore. The name of methode of mineral processing to extract Gold is Amalgamation method. Amalgamation method used tromol that had ball or rod iron inside. The function of them is look like a ball mill to crush and grind the Gold ore.Using Mercury is an easy way to extract the Gold, but, in the other hand, Mercury had been a negative effect that it has been to be continued for along times future. The complexity problems of Mercury could not to be handle by one country or one government, it must to be handled by international and global relationships. Keywords : Environment, Extraction, Heavy Metal, Mercury, Pollutant